The role of internal audit in corporate governance. (Journal of Economic Research & Business Administration, 2016)
Corporate relations revived in Kazakhstan recently. We have not yet accumulated its own experience in managing joint-stock companies, solve problems related to differences in the interests of owners and managers, minority and majority shareholders, the protection of property rights and shareholders as a whole. You can certainly take advantage of other people’s experiences, simply copying approaches and positions that we offer recommendations to the international community for Corporate Governance. But for all those similarities that dictates shareholder ownership companies in the world, there are significant differences that must be considered. Principles of Corporate Governance of the Organization for Economic Cooperation and Development (OECD) define corporate governance as the distribution of rights and responsibilities among the various components of corporate devices - board, administrative staff, shareholders and other stakeholders - and defines the rules and procedures of decision-making. Due to this, a system of determining the goals and objectives of the corporation, means of implementation of tasks and tracking performance.
Keywords: corporate management; shareholders; investors.